The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1994
DOI: 10.1103/physrevlett.73.2444
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Noninductive Current Profile in Tokamak Plasmas

Abstract: The noninductive part of the measured current profile has been determined for DIII-D plasmas. A technique for determining the flux surface average of the quantity K~B and a model for the resistivity separates the current profile into inductive and noninductive portions. Analysis (1) where the cylindrical coordinate system (R, Z, @) is used, P = -fo BzR'dR' is the total poloidal flux per radian inside a major radius R, and F(p) = RB~. Furthermore, it is assumed that toroidally symmetric, nested fiux surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
125
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 131 publications
(135 citation statements)
references
References 10 publications
9
125
0
Order By: Relevance
“…At this time, the plasma current is supplied by bootstrap (59%), NBCD (31%), and ECCD (8%) [7]. The measured [14] noninductive current fraction f NI = 99.5% is in reasonable agreement with that calculated by summing the individual contributions. The relatively small contribution from ECCD is very important, as both calculation and previous experience [1] shows that without it, the inductive current would gradually peak near the mid-radius.…”
Section: % Noninductive Operation With Weak Negative Shearsupporting
confidence: 71%
See 1 more Smart Citation
“…At this time, the plasma current is supplied by bootstrap (59%), NBCD (31%), and ECCD (8%) [7]. The measured [14] noninductive current fraction f NI = 99.5% is in reasonable agreement with that calculated by summing the individual contributions. The relatively small contribution from ECCD is very important, as both calculation and previous experience [1] shows that without it, the inductive current would gradually peak near the mid-radius.…”
Section: % Noninductive Operation With Weak Negative Shearsupporting
confidence: 71%
“…The noninductive current is directly calculated from the equilibrium using the method described in Ref. [14].…”
Section: % Noninductive Operation With Weak Negative Shearmentioning
confidence: 99%
“…The loop voltage was reduced to near zero and the net noninductive fraction of 100% was achieved. However, internal loop voltage ͑VLOOP͒ analysis 17 indicated that local inductive current was not zero near the plasma center. The negative inductive current there is a reaction to excessive NBCD near the axis which led to neutral beam overdrive near the axis and an increase in the central current density.…”
Section: Characteristics Of 100% Noninductive High ␤ Dischargesmentioning
confidence: 99%
“…2͑a͒.The inductive current is the product of the neoclassical conductivity and parallel electric field. 17 The latter is calculated from the time derivative of the poloidal flux based on a series of equilibrium reconstructions using the equilibrium fitting code, EFIT, 18 and is rather insensitive to the parameterization used in EFIT. The total current density profile is sensitive to this parameterization since it is calculated from the spatial derivatives of the poloidal flux.…”
Section: Characteristics Of 100% Noninductive High ␤ Dischargesmentioning
confidence: 99%
“…[16][17][18][19][20] The neoclassical bootstrap current arises from the particle orbit excursion across radial pressure gradient. It has been known that source of the current is mostly the trapped particles, but the current is carried mostly by the passing particles via collisional coupling between trapped and passing particles.…”
Section: Introductionmentioning
confidence: 99%